Back Cover: Synthesis, Structure, and Reactivity of Lewis Base Stabilized Plumbacyclopentadienylidenes (Chem. Eur. J. 50/2013). Issue 50 (9th December 2013) - Saito, Masaichi; Akiba, Tomoki; Kaneko, Misumi; Kawamura, Toshiaki; Abe, Minori; Hada, Masahiko; Minoura, Mao
<x xml:space="preserve">Abstract</x> Plumbacyclopentadienylidenes in which the lead atom is coordinated to a variety of Lewis bases, including THF, exhibit interesting behavior and reactivity. In their Full Paper on page 16946 ff., M. Saito et al. show that the THF adduct, which is a rare example of a 10‐X‐4 species, reacts with trifluoroborane or trichlorogallane to afford fluoroborole and chlorogallole, respectively.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>